2020
DOI: 10.3991/ijim.v14i11.13891
|View full text |Cite
|
Sign up to set email alerts
|

Improving Second Language Speaking and Pronunciation through Smartphones

Abstract: The ability to speak English fluently and confidently plays a vital role in enhancing employment opportunities of graduate students of India. Though English has been a second language for over decades in the country, teaching speaking skills with intelligible pronunciation to the first generation of learners remains a major challenge. The limited number of classes allotted for English speaking and pronunciation and lack of resources make it more challenging. Previous research suggests that Mobile Assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
2
6
0
1
Order By: Relevance
“…These findings seem to support previous studies that suggest learning content management subsystem are one of the essential components for the mobile learning system [7]. Furthermore, it was found that mobile technologies help learners to access language learning materials easily [8], and this had a knock-on effect to increase interests in language learning. Another study confirms this, as their findings showed that the application of mobile technologies in teaching increases student focus, develops students' skills and nurture positive acceptance of mobile learning [9].…”
Section: Discussionsupporting
confidence: 89%
“…These findings seem to support previous studies that suggest learning content management subsystem are one of the essential components for the mobile learning system [7]. Furthermore, it was found that mobile technologies help learners to access language learning materials easily [8], and this had a knock-on effect to increase interests in language learning. Another study confirms this, as their findings showed that the application of mobile technologies in teaching increases student focus, develops students' skills and nurture positive acceptance of mobile learning [9].…”
Section: Discussionsupporting
confidence: 89%
“…Increasing the awareness of practicing speaking skills through the smartphone (for example using a video chat with other peers) among the EFL learners would possibly stimulate their interest in developing speaking via smartphones. Although several papers attempted to investigate the development of speaking skills using smartphones (see, for example, Darmi and Albion, 2017;Sherine, Sastry and Seshagiri, 2020), exploring the enhancement of oral skills and subskills using smartphones is a matter that requires attention of teachers and researchers in the future studies.…”
Section: Out-of-the-classroom Statementsmentioning
confidence: 99%
“…Two studies have examined the potential use of WhatsApp, as an asynchronous CMC tool, to improve language learners' speaking skill (Andújar-Vaca & Cruz-Martínez, 2017;Akkara, Anumula & Mallampalli, 2020). Andújar-Vaca and Cruz-Martínez (2017) used WhatsApp as an extra-curricular activity to teach speaking to Spanish language learners for six months.…”
Section: Whatsapp and Language Teachingmentioning
confidence: 99%